1998
DOI: 10.1021/ac971369i
|View full text |Cite
|
Sign up to set email alerts
|

QCM Response to Solvated, Tethered Macromolecules

Abstract: When the quartz crystal microbalance (QCM) is operated in contact with solution and used to detect inertia increases caused by macromolecules binding to its surface, resonance frequency shifts are reported in the literature to be greater than, less than, and the same as an identical macromolecular mass would cause as a dry layer. A previous report of wet and dry M13 DNA giving the same, linear frequency versus mass response is examined. The M13 data are shown to follow the reciprocal of the square root of mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 19 publications
1
41
0
2
Order By: Relevance
“…A desirable, user-demanded detection limit is ca. 10 -18 M, depending on the number of base pairs [51]. In order to minimize the detection limit of a functionalized resonator surface, quartz crystals with higher resonance frequencies were used, and multilayers composed of nucleic acids and polymers/proteins were developed [46].…”
Section: Dna/rna-based Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A desirable, user-demanded detection limit is ca. 10 -18 M, depending on the number of base pairs [51]. In order to minimize the detection limit of a functionalized resonator surface, quartz crystals with higher resonance frequencies were used, and multilayers composed of nucleic acids and polymers/proteins were developed [46].…”
Section: Dna/rna-based Biosensorsmentioning
confidence: 99%
“…Steric hindrance of the hybridization reaction explains this low value; however, the equivalence of mass change and frequency in the detection of nucleic acids in solution is questionable. Although the translation of the frequency shift into mass using the Sauerbrey equation is pursued in many publications, one should refer to papers by Thompson and co-workers [50,[57][58][59] and Fawcett et al [51], who showed that oligonucleotides immobilized on the resonator surface in fluids do not behave like an ideal rigid mass. Thompson and co-workers revealed, for example, that the serial resonance upon binding of DNA exhibits a frequency change that is 18 times larger than predicted by the Sauerbrey equation.…”
Section: Dna/rna-based Biosensorsmentioning
confidence: 99%
“…doi:10.1016/j.bios.2011.03.002 advantages such as simplicity, no requirement for labeling of the analytes (Pan and Rothberg, 2005), higher sensitivity as compared with other type of DNA biosensors based on the surface plasmon resonance (SPR) or quartz crystal microbalance (QCM) techniques . SPR is one kind of optical methods based on the measurement of changes in the refractive index due to the mass adsorption on the sensor chip surface (Kobori et al, 2004 QCM measures the change in frequency of a vibrating crystal due to the binding of molecules to the crystal (Fawcett et al, 1998). The detection limits of SPR and QCM are ∼10 −9 ) and 10 −10 M (Feng et al, 2007), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Die erste In-situ-Messung in Lösung erfolgte mit einem akustischen Plattenschwinger [44] und die zweite mit einem Dickenscherschwinger, an den eine Einzelstrang-DNA über eine selbstorganisierte 11-Sulfanylundecanolschicht an die Goldoberfläche gebunden war. Die angestrebte und von Anwendern geforderte untere Nachweisgrenze liegt je nach Zahl der Basenpaare bei etwa 10 À18 m. [68] Um die Nachweisgrenze der funktionalisierten Resonatoroberflächen zu erniedrigen, wurden Quarze mit höherer Resonanzfrequenz verwendet, Mehrschichtsysteme aus Nucleinsäuren und Polymeren/Proteinen entwickelt, [63] DNA-Dendrimere synthetisiert [69] und die Nucleinsäuren durch Polymerasekettenreaktion (PCR) an der Oberfläche amplifiziert. Die gängigen Verfahren beruhen auf der Modifizierung der Phosphatgruppe des 5'-Endes durch Einführung von Schwefelgruppen.…”
Section: Adsorption Vonunclassified